High‐Performance Thickness Insensitive Perovskite Solar Cells with Enhanced Moisture Stability - Chen, Jiehuan; Zuo, Lijian; Zhang, Yingzhu; Lian, Xiaomei; Fu, Weifei; Yan, Jielin; Li, Jun; Wu, Gang; Li, Chang‐Zhi; Chen, Hongzheng (Advanced energy materials, 2018)
High‐performance perovskite solar cells (PVSCs) with absorber layer thickness insensitive features are important for practical fabrication, however these features are difficult to be realized. There are very few reports of the fabrication of polycrystalline PVSCs with power conversion efficienies (PCE) insensitive to film thickness beyond 600 nm. The main reason lies in more serious recombination of the thick perovskite layer compared to the thin layer. Herein, this challenge is addressed by a simple hot casting method to formulate high‐quality perovskite film with enlarged grain size, high carrier mobility, and reduced defects. It is found that increasing the temperature to 70 °C can dramatically increase the film thickness and enlarge the perovskite crystal, therefore boost the efficiency from ≈16% to ≈19%. Notably, a record PCE of 19.54% is achieved with 850 nm thick perovskite film, which is among the highest efficiency for thick‐film PVSCs. The PCE remains steady around 19% when modifying the perovskite layer from 700 to 1150 nm. Moreover, these thick‐film PVSCs show good stability with 80% of its initial efficiency after 30 d in air with a humidity of 50%. Overall, this simple yet effective method has a great potential in the mass manufacture of PVSCs. High‐performance thickness insensitive perovskite solar cells (PVSCs) with enhanced moisture stability are demonstrated via a simple hot casting method, which formulates high‐quality perovskite film with enlarged grain size, high carrier mobility, and reduced defects. A record power conversion efficiency of 19.54% is achieved with 850 nm thick perovskite film, which is among the highest efficiency for thick‐film PVSCs.